An integrated approach of unit trust and waqf as a sustainable investment conceptual model in the Covid-19 era - Sulaiman, Syahnaz; Hasan, Aznan (International Journal of Liberal Arts and Social Science, 2020)
Harnessing a sustainable model of waqf remains as the key challenge faced by waqf managers, particularly in the mid of socio-economic crisis due to the COVID-19 pandemic. The aim of this paper is to discuss and propose the potential viability of waqf unit trust as a form of an alternative asset for the purpose of waqf creation. The current study employed a qualitative research approach, which was designed through the use of document analysis of classical Islamic books, Islamic ruling (fatwa), journal articles, books, online resources, and policy documents. The novelty of the model proposed in this paper can be traced in its highlight of the significance of the investment strategy of waqf in the effort to ensure returns that are sustainable for waqf, particularly during this difficult time in reducing the socioeconomic impacts of the COVID-19 catastrophe, that is through the introduction of a conceptual model of waqf unit trust as a potential mechanism to accumulate more waqf in the form of cash from individual investors. This paper emphasizes that waqf plays a significant role as a global financial cure for economic revival post the COVID-19 pandemic. The capital waqf assets‟ sustainability in the form of unit trust is preserved through the distinctive fixed price feature of the waqf unit trust as proposed prior to the conclusion of this paper.